Eksistensi Tradisi Hajat Bumi Cariu di Desa Sukadana Kecamatan Sukadana Kabupaten Ciamis - Ahmad Rizky Fauzi (Jurnal Artefak, 2023)
This research aims to find out when Hajat Bumi Cariu existed, and the procession, benefits, and values contained in it. In the oral tradition of the Cariu community, Hajat Bumi has existed since hundreds of years ago (approximately 500 YA) since the era of Prabu Sirnaraja, king of Samida, Rajadesa son of Prabu Siliwangi IV (Jayadiningrat). Hajat Bumi tradition consists of 1) Pre-Implementation, 2) Implementation and 3) a Closing Meeting after the event is over. In the beginning, the desire for the earth was interpreted as a ritual or a tradition of asking God for salvation. Then, along with the development of the Hajat Bumi period, apart from being a story, it is also a form of gratitude to Almighty God for the abundant harvest, the event is regularly held every two years every Muharram month because in the past that month was when the harvest arrived precisely on the day between Monday or Thursday. The background of the writing of this article is based on the condition of the social crisis of the community that destroys a nation, while in tradition it can be a media to strengthen social bonds between communities so that a society that is compact and cooperates is realized. The research method used is a qualitative method with a descriptive approach. The research consists of The research method consists of several stages, namely, the pre-field stage, the work stage in the field, and the analysis stage in the field. The data collection technique used in this research uses observation, interview, and documentation. In this research, the author uses primary data sources and secondary data sources. The results of the research show that the people of Cariu and its surroundings still hold fast to the cultural heritage that has existed for a long time and apply the values that exist in it such as always maintaining the sustainability of nature, always being grateful and praying to the Almighty God, and maintaining cooperation.